2D–3D radiograph to cone-beam computed tomography (CBCT) registration for C-arm image-guided robotic surgery - Liu, Wen Pei (Int J Comput Assist Radiol Surg, 2014)
PURPOSE: C-arm radiographs are commonly used for intraoperative image guidance in surgical interventions. Fluoroscopy is a cost-effective real-time modality, although image quality can vary greatly depending on the target anatomy. Cone-beam computed tomography (CBCT) scans are sometimes available, so 2D–3D registration is needed for intra-procedural guidance. C-arm radiographs were registered to CBCT scans and used for 3D localization of peritumor fiducials during a minimally invasive thoracic intervention with a da Vinci Si robot. METHODS: Intensity-based 2D–3D registration of intraoperative radiographs to CBCT was performed. The feasible range of X-ray projections achievable by a C-arm positioned around a da Vinci Si surgical robot, configured for robotic wedge resection, was determined using phantom models. Experiments were conducted on synthetic phantoms and animals imaged with an OEC 9600 and a Siemens Artis zeego, representing the spectrum of different C-arm systems currently available for clinical use. RESULTS: The image guidance workflow was feasible using either an optically tracked OEC 9600 or a Siemens Artis zeego C-arm, resulting in an angular difference of Δθ : ~ 30°. The two C-arm systems provided TRE(mean) ≤ 2.5 mm and TRE(mean) ≤ 2.0 mm, respectively (i.e., comparable to standard clinical intraoperative navigation systems). CONCLUSIONS: C-arm 3D localization from dual 2D–3D registered radiographs was feasible and applicable for intraoperative image guidance during da Vinci robotic thoracic interventions using the proposed workflow. Tissue deformation and in vivo experiments are required before clinical evaluation of this system.